Combined transcriptome and metabolome reveal glutathione metabolism plays a critical role in resistance to salinity in rice landraces HD961 - Yang, Shan; Liu, Mengshuang; Chu, Na; Chen, Guanxiu; Wang, Panpan; Mo, Junjie; Guo, Haifeng; Xu, Jianghuan; Zhou, Hongkai (Frontiers in Plant Science, 2022)
Rice is one of the most important food crops around the world, but is a moderate salt-sensitive crop that easily suffers salt stress. In order to detect the different salinity tolerance between HD961 and 9311 strains of rice during the seedling stage, a combined transcriptome and metabolome analysis was performed. The results showed that the growth potential and antioxidant ability of HD961 were stronger than 9311 under salt stress (SS). An analysis of transcripts showed that total DEGs from 6145, 3309, 1819, and 1296 strains were identified in the groups of TH60, TH120, T60, and T120, respectively. Biosynthesis of secondary metabolites, starch and sucrose metabolism, metabolic pathways, and phenylpropanoid biosynthesis were shared in the four treatment groups based on a KEGG enrichment analysis of DEGs. In addition, alpha-linolenic acid metabolism, plant hormone signal transduction, plant-pathogen interaction, and fatty acid elongation were specific and significantly different in HD961. A total of 92, 158, 151, and 179 SRMs responded to SS in MH60, MH120, M60, and M120, respectively. The KEGG analysis showed that eight common metabolic pathways were identified in the 4 treatment groups, of which biosynthesis of amino acids was most significant. Three specific metabolic pathways were identified in the HD961 strain, including glutathione metabolism, ascorbate and aldarate metabolism, and pantothenate and CoA biosynthesis. Integrative analysis between the transcriptome and metabolome showed that glutathione metabolism was specific and significantly affected under SS in HD961. A total of 7 SRMs and 48 DEGs as well as 4 SRMs and 15 DEGs were identified in the glutathione metabolism pathway in HD961 and 9311 strains, respectively. Pearson correlation analysis showed that there was significant correlation between reduced glutathione and 16 genes (12 up-regulated and 4 down-regulated genes), suggesting these genes could be candidates as salt-tolerance regulation genes. Collectively, our data show that glutathione metabolism plays a critical role in the response to SS in rice. Moreover, the stronger regulative ability of related common genes and metabolites might contribute to salt resistance in HD961.